When and How Different Motives Can Drive Motivated Political Reasoning. Issue 5 (24th April 2020) - Bayes, Robin; Druckman, James N.; Goods, Avery; Molden, Daniel C.
Abstract : It is commonly assumed that the effectiveness of political messages depends on people's motivations. Yet, studies of politically motivated reasoning typically only consider what partisans generally might want to believe and do not separately examine the different types of motives that likely underlie these wants. The present research explores the roles of distinct types of motives in politically motivated thinking and identifies the conditions under which motivated reasoners are persuaded by political messages. Results of an experiment with a large, representative sample of Republicans show that manipulations inducing motivations for either (1) forming accurate impressions, (2) affirming moral values, or (3) affirming group identity each increased beliefs in and intentions to combat human‐induced climate change, but only when also paired with political messages that are congruent with the induced motivation. We also find no evidence of a backlash effect even when individuals are provided with clearly uncongenial information and a motivation to reject it. Overall, our findings make clear that understanding when and why motivated political reasoning occurs requires a more complete understanding of both which motivations might be active among a group of partisans and how these motivations resonate with the messaging they receive.